70.0k views
0 votes
G(x)=(-5x-1) (2x+8)
Please help!​

User Caub
by
4.7k points

2 Answers

4 votes

Answer: g(x)= -10x2-42x-8

Explanation:

G(x)=(-5x-1)(2x+8)

Open the bracket

G(x)=(-10x2-40x-2x-8)

G(x)=(-10x2-42x-8)

G(x)= -(10x2+42x+8)

User Knaser
by
4.2k points
1 vote

Answer:


g(x) = -10x^2 - 42x - 8

Explanation:

Step 1: FOIL out


g(x) = (-5x - 1)(2x + 8)


g(x) = (-5x * 2x) + (-5x * 8) + (-1 * 2x) + (-1 * 8)


g(x) = -10x^2 - 40x - 2x - 8


g(x) = -10x^2 - 42x - 8

Answer:
g(x) = -10x^2 - 42x - 8

User Paolo B
by
4.2k points